Highly active recyclable SBA-15-EDTA-Pd catalyst for Mizoroki-Heck, Stille and Kumada C-C coupling reactions - Rathod, Jayant; Sharma, Priti; Pandey, Punam; Singh, A. P.; Kumar, Pradeep (Journal of Porous Materials, 2017)
Highly efficient SBA-15-EDTA-Pd(11) heterogeneous catalyst was synthesized by covalent anchoring Pd-EDTA complex over organo-modified surface of SBA-15. SBA-15-EDTA-Pd(11) catalyst was found to exhibit excellent catalytic activity in appreciable yield for Heck, Stille and Kumada cross-coupling reactions. Catalytic system exhibited excellent activity for completion of reaction, isolation, Pd loading (0.87 mmol%) and yields of products as compared to earlier reported heterogeneous supported Pd catalysts. Covalently anchored heterogeneous SBA-15-EDTA-Pd(11) catalyst can be recycled for more than five times without noticeable loss in activity and selectivity.